2019
DOI: 10.1029/2018gl080813
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dynamic Contribution to Future Changes in Tropical Precipitation From Low‐Level Convergence Lines

Abstract: Future precipitation changes include contributions from both thermodynamic and dynamic processes. Given that precipitation in the tropics is commonly associated with convergence lines, we construct a simple linear regression model relating the convergence line frequency and strength to precipitation at subdaily time scales, and use it to show that changes in the convergence lines are related to the dynamic change in the precipitation. Given GCM‐predicted convergence line changes, we predict precipitation chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In regions such as extratropical latitudes where the thermodynamic effects (changes in atmospheric moisture) are dominant (Chen et al, 2019), the extreme precipitation-temperature scaling rate is close to the C-C rate. Wherever the dynamic factors (changes in atmospheric circulations) come into play such as tropical and subtropical latitudes, the scaling rate is deviated from the C-C rate (Weller et al, 2019;Norris et al, 2020). The overall latitudinal pattern of the extreme precipitation-temperature scaling rate is in line with a previous study based on an empirical distribution (Tabari et al, 2019).…”
Section: General Pattern Of Changessupporting
confidence: 88%
“…In regions such as extratropical latitudes where the thermodynamic effects (changes in atmospheric moisture) are dominant (Chen et al, 2019), the extreme precipitation-temperature scaling rate is close to the C-C rate. Wherever the dynamic factors (changes in atmospheric circulations) come into play such as tropical and subtropical latitudes, the scaling rate is deviated from the C-C rate (Weller et al, 2019;Norris et al, 2020). The overall latitudinal pattern of the extreme precipitation-temperature scaling rate is in line with a previous study based on an empirical distribution (Tabari et al, 2019).…”
Section: General Pattern Of Changessupporting
confidence: 88%
“…We propose that this simple argument suggests that there must exist a breakdown scale of the water budget constraint on precipitation-L WB . Below L WB the system is "free," and the magnitude of precipitation changes could be much larger than the evaporation changes (the dynamic contribution can dominate; Allen & Ingram, 2002;Chadwick et al, 2013;Ma & Xie, 2013;O'Gorman, 2015;Pfahl et al, 2017;Sato et al, 2017;Weller et al, 2019). However, above L WB , the precipitation changes are limited by the evaporation changes.…”
Section: Discussionmentioning
confidence: 99%
“…The above argument can also be put in a more commonly used perspective of thermodynamics vs. dynamics contributions to changes in precipitation (which has some similarities but is not identical to the water budget perspective presented above; Allen & Ingram, ; Bony et al, ; Ma & Xie, ; O'Gorman, ; Pfahl et al, ; Sato et al, ; Weller et al, )). It is argued that the main contributions to precipitation changes are changes in air temperature and hence in water vapor amount in the atmosphere (thermodynamics contribution), and changes in the atmospheric circulation (dynamic contribution).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that changes to tropical precipitation can be usefully decomposed into the contributions from both thermodynamic and dynamic processes (e.g., Weller et al, 2019), and the decomposition methodology of Chadwick et al (2013, 2016) can be used to quantify the relative contribution of these two terms (Chadwick et al, 2016; Kent et al, 2015; Lazenby & Todd, 2018; Monerie et al, 2019). Using this method, changes in tropical precipitation, under climate change, have been largely related to changes in the dynamical component which indicate shifts in the position of convection (e.g., Chadwick et al, 2016; Kent et al, 2015).…”
Section: Introductionmentioning
confidence: 99%